10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
ObjectivesEvidence suggests individuals with a laryngectomy (IWL) face multiple challenges accessing the necessary multidisciplinary healthcare professionals (HCPs) needed to provide optimal care. This study examined the perceptions of HCPs regarding current laryngectomy care models to identify and prioritize opportunities for service improvement.MethodsA concept mapping methodology was utilized, which combines both qualitative and quantitative data, enabling HCPs to identify and then prioritize critical elements of care that require refinement to improve the current care pathway. Twenty HCPs were recruited from 2 services within the United States (10 per site) including participants from medical, nursing and allied health disciplines. Considering differences in services, separate analysis was conducted by site.ResultsParticipants generated 31 and 36 unique statements from each site respectively. Both sites identified highly similar issues. Go-Zone analysis revealed 49% of Site 1 statements and 33% of Site 2 rated highest for both importance and changeability. Prioritized issues related to the importance of education, access to skilled HCPs, coordinated services, the need for a post-acute care pathway and improving financial supports.ConclusionsHCPs identified multiple actionable changes to help optimize the care pathway for IWLs which can be used by services to direct improvements in care.